Osteoblast response (initial adhesion and alkaline phosphatase activity) following exposure to a barrier membrane/enamel matrix derivative combination - Thangakumaran S; Sudarsan Sabitha; Arun K; Talwar Avaneendra; James Johnson (Wolters Kluwer Medknow Publications, 2009)
Background and Objective: The enamel matrix derivative (EMD) has been used in combination with barrier membranes to optimize regeneration in vertical osseous defects. However, the osteoblast response when exposed to the EMD/barrier membrane combination has not yet been evaluated. The osteoblast behavior when exposed to a combination of regenerative materials must be evaluated to fully understand their effect on bone regeneration. Therefore, the present study was undertaken to estimate the initial adhesion and alkaline phosphatase (ALP) activity of an osteoblast cell line (SaOS-2) when exposed to four commercially available resorbable membranes and determine if the addition of EMD had any modulatory effect on osteoblast behavior. Materials and Methods: 5 x 104 SaOS-2 cells between passages 7-10 were cultured in two 24-well culture plates. Plate A was used for the adhesion assay and Plate B was used for the ALP assay. A MTT (3-[4, 5-dimethylthiazolyl-2]-2, 5-diphenyltetrazolium bromide) assay was done after 24 hours to determine the adhesion of the osteoblastic cells to four barrier membranes: 1) a non cross-linked porcine Type I and III collagen membrane (BG), 2) a weakly cross-linked Type I collagen membrane (HG), 3) a glutaraldehyde cross-linked bovine Type I collagen (BM), and 4) a resorbable polymer membrane (CP). Osteoblast differentiation was studied using an ALP assay with p-nitro phenyl phosphate as the substrate at 24 hours, 72 hours, and 1 week. A total of 50 µg/ml of EMD dissolved in 10 mM acetic acid was added into each well and the entire experimental protocol outlined above was repeated. Results: The osteoblast adhesion to collagen barriers showed a statistically insignificant reduction following the addition of EMD. Adhesion to the polymer barrier, although significantly lower when compared with collagen barriers, was unaffected by the addition of EMD. ALP activity after 1 week among the various groups was as follows: EMD alone (75.59±2.5)>EMD/BG(64.78±3.04)>EMD/HG(55.40±3.89)≈EMD/BM(54.75±4.17)>BG (51.32±2.76)>HG(49.92±2.4)>BM(48.14±1.4)>Control(46.29±1.39)>EMD/CP (37.46±3.54)>CP(32.12±1.49) Conclusion: There was no additive effect on osteoblast adhesion/ALP activity following exposure to an EMD/polymer combination. EMD/collagen positively influences osteoblast differentiation in a time dependent manner.